IbM KELOMPOK USAHA RUMAH TANGGA TERASI REBON DI LINGKUNGAN PANTAI TELENG KOTA PACITAN - Tjahjo Purtomo; Ida Aju Brahma Ratih; Djoko Budi Utomo (JPM17: Jurnal Pengabdian Masyarakat, 2016)
Pacitan is geographically part of the coastal area is. These waters have avery great potential for fisheries and abundant. For the people who live incoastal areas, the existence of fisheries resources affects the pattern ofpeople's livelihoods. The results of the fishery generally have a short and quicksave damaged. One of the results of processing of fisheries in the form ofmaking shrimp paste. Shrimp paste is a product of small fish preservation orrebon who has processed. One of the Central coastal fishing village in Pacitanis Environment brought in a Village, Subdistrict Teleng of Pacitan. In theneighborhood there are Teleng 2 (two) business household maker of shrimppaste. Shrimp paste maker household business which became the object of thescience and technology grant programs for the Community (IbM) is a smallbusiness households belonging to Bu Tukiyem and Bu Miskinem. At this timethe Efforts of households making shrimp paste is still done traditionally,ranging from shrimp paste manufacture equipment used to the management ofthe business and its marketing, namely by selling products to market its ownproducts by entrusting to the stalls in the market village and stalls on site toursTeleng Ria Beach and wait for orders to come, or selling shrimp paste towholesalers, so that their products are packaged and marketed with labels thatwholesalers. The science and technology programme for the Community(IbM), expected to raise shrimp paste products, as well as with theconstruction of a simple Management, expected employers to increase shrimppaste market.Keywords: Shrimp Paste Rebon Teleng Pacitan